ANALISIS PROSEDUR AUDIT ATAS PERSEDIAAN CV. ABADI OLEH KAP XYZ - Rabbani, Sulthon Falih Rasyid; Jannah, Binti Shofiatul (Cahaya Ilmu Bangsa, 2024)
Inventory management is crucial for companies as it directly impacts financial reporting. However, inventory is prone to misstatements, making inventory audits essential for ensuring the reliability of inventory information. This study focuses on KAP XYZ's audit procedures at CV. Abadi (pseudonym), a trading company dealing with building materials, which faced significant discrepancies in inventory records. The qualitative descriptive method was employed to explore the audit process through observations and interviews. The findings revealed a staggering 59% loss in inventory compared to the recorded figures, indicating potential misappropriation or recording errors. Recommendations include enhancing warehouse security, improving inventory categorization, and providing staff training to mitigate future discrepancies.